(untitled) (Research, Society and Development, 2021)
The Fourth Industrial Revolution extended digital transformation to the educational environment by reconfiguring the labor market and requiring new skills and skills from professionals. Thus, Education 4.0 proposes the insertion of new technologies in the educational environment so that the teaching-learning process transcends traditional education by boosting innovative teaching and learning by doing, opening space for learning based on experimentation, project development and experiences. In this scenario, educational robotics presents itself as a pedagogical resource capable of assisting the technological-digital transition of education. The objective of this research is to analyze educational robotics as a pedagogical resource able to attribute to teaching and learning current resources towards Education 4.0. For this, a bibliometric analysis of word co-occurrence was developed, aiming to survey the main terms related to educational robotics present in the literature and understand the expansion of robotics as a pedagogical resource over the years. The results showed that robotics as a pedagogical resource is in full expansion promoting learning by experimentation, being associated with computational thinking, constructivist and constructionist learning theories and promoting teaching based on problem solving. Characterized as a current pedagogical resource capable of providing a multidisciplinary learning environment favoring digital integration in the daily life of students and the incorporation of skills and attitudes able to prepare them for the full exercise of citizenship in a constantly evolving society.